The role of emotional intelligence in interpersonal conflicts management in professional environment - N. A. Givargizova (Вестник университета)
The article studies complex interplay of emotional intelligence (hereafter – EI) and its key role in managing interpersonal conflict in professional settings. The study elucidates how EI subtle components such as self-awareness, empathy, self-regulation, and social skills play an important role in deciphering and overcoming the emotional complexities inherent in professional conflicts. Through methodical research, the quintessential role of EI in creating a harmonious workplace has been revealed, where conflicts are not only effectively resolved but also transformed into opportunities for growth. At the same time, the critical role of empathy in understanding and appreciating emotional states of others has been emphasized, thus fostering more inclusive and empathic communication. The practice segment of the study offers a number of strategies and training programs aimed at developing EI in professionals. These techniques, ranging from mindfulness meditation to empathy mapping workshops and emotional intelligence training, offer actionable ways to increase emotional competence in a variety of professional situations. The article concludes by discussing practical applicability of these ideas in a variety of professional settings, suggesting directions for future research, including the study of EI in different cultural contexts and technology integration into EI trai ning. This comprehensive study not only contributes to the academic discourse on EI, but also serves as a beacon for organizations and individuals seeking to navigate the emotional landscape of today’s professional environments.